Forced degradation studies on atazanavir and cobicistat by rp-hplc method - PRATIK K. VORA; SURESH C AMETA; MRUNAL K SHIRSAT (International Journal of Pharma and Bio Sciences, 2017)
The objective of the current study was to conduct forced degradation studies of Atazanavir and Cobicistat drug substances in order to identify whether the developed HPLC method is capable to accurately estimate the drug content and its degradation products in higher stress conditions. Forced degradation study was carried out to evaluate the degradation pattern, intrinsic stability of the molecule and to verify that the analytical procedures used for Assay and Related Substances are stability indicative.These studies provide information and discrimination between process related, degradant related and degradants from drug-excipient combination. If the drug product does not show any degradation when it was exposed to stress conditions, further stress study is unnecessary.Atazanavir and Cobicistat drug substance samples were subjected to forced degradation under different stress conditions such as Acid degradation (0.1N HCl, 1 mL at 70°C for 3 hours), Base degradation (0.1N NaOH, 1 mL at 70°C for 3 hours), Oxidation (3% H2O2, 2 mL at 70°C for 3 hours), Photo Degradation (For 4 days) and Thermal degradation (1 mL at 110°C for 3.5 hours). The stressed samples were analyzed using a reversed-phase HPLC method.